2021
DOI: 10.1002/jia2.25747
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 pharmacokinetics and safety study of extended duration dapivirine vaginal rings in the United States

Abstract: Introduction Vaginal rings are a promising approach to provide a woman‐centred, long‐acting HIV prevention strategy. Prior trials of a 25 mg dapivirine (DPV) ring have shown a favourable safety profile and approximately 30% risk reduction of HIV‐1 infection. Extended duration rings replaced every three months may encourage user adherence, improve health service efficiency and reduce cost overall. We evaluated safety, pharmacokinetics, adherence and acceptability of two three‐month rings with diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…However, the 1-month ring had consistently higher ratings throughout the study. Although there were no safety concerns identified, and no differences in grade ≥2 genitourinary adverse events between arms, 14 participants using the 3-month ring reported more changes to the vaginal environment, and they expressed concerns about the hygiene and safety of a ring left in place for so long.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the 1-month ring had consistently higher ratings throughout the study. Although there were no safety concerns identified, and no differences in grade ≥2 genitourinary adverse events between arms, 14 participants using the 3-month ring reported more changes to the vaginal environment, and they expressed concerns about the hygiene and safety of a ring left in place for so long.…”
Section: Discussionmentioning
confidence: 93%
“…However, for the 1-month ring, acceptability findings from phase 1 and 2 studies with lower risk women 18 , 24 , 40 largely predicted those from larger studies among higher risk women, 20 , 22 , 41 and participants in the current study reported that they would be highly likely to use the ring if it were found effective. 14 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ring remains in‐situ until it is removed at the end of the month. A 90‐day ring has additionally been evaluated in a phase 1 study [ 36 ]. Two RCTs with the DVR ring indicated an overall efficacy of 30%, and effectiveness improved to 50% when the trial was converted to open label and adherence was improved [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%